Photoelectrocatalytic oxygen evolution reaction on visible-light irradiated W-doped alkali niobate-based perovskite - Praxedes, Fabiano R. [UNESP]; Nobre, Marcos A.L. [UNESP]; Olean-Oliveira, André [UNESP]; Portugal, Miquéias L. [UNESP]; Poon, Po S.; Teixeira, Marcos F.S. [UNESP]; Lanfredi, Silvania [UNESP]; Matos, Juan (Elsevier, 2023)
The photoelectrocatalytic oxygen evolution reaction was studied under visible-light irradiated W-doped niobate-based perovskites. Nanostructured K0.5Na0.5(WxNb1−x)O3 materials were prepared by ultrasonic spray pyrolysis as a function of 1 – 3 mol% W6+ cations within the host structure. A careful characterization of solids including morphology, structure, texture, optical, and electrochemical properties was performed. From the characterization analysis it can be concluded the materials are constituted by nanostructured mesoporous hollow spheres and the substitution of Nb by W leads to the distortion of NbO6 octahedra. The photoelectrocatalytic activity was correlated with the structural properties and electrochemical properties of materials. To the best of our knowledge, the present W-doped niobate-based perovskites showed the highest turnover frequency reported in the photoelectrocatalytic OER under similar overpotential conditions. Accordingly, this new class of perovskite-based crystalline materials opens a door for the scaling-up of catalytic and photocatalytic processes related to energy production.
Keywords: Alkali niobate perovskite; Oxygen evolution reaction; Photoelectrocatalysis; Tungsten-doping